Impact of cobalt and proline foliar application for alleviation of salinity stress in radish - Inayat, Hira; Mehmood, Hassan; Danish, Subhan; Alharbi, Sulaiman Ali; Ansari, Mohammad Javed; Datta, Rahul (BMC plant biology, 2024)
Salinity stress ranks among the most prevalent stress globally, contributing to soil deterioration. Its negative impacts on crop productivity stem from mechanisms such as osmotic stress, ion toxicity, and oxidative stress, all of which impede plant growth and yield. The effect of cobalt with proline on mitigating salinity impact in radish plants is still unclear. That's why the current study was conducted with aim to explore the impact of different levels of Co and proline on radish cultivated in salt affected soils. There were four levels of cobalt, i.e., (0, 10, 15 and 20 mg/L) applied as CoSO4 and two levels of proline (0 and 0.25 mM), which were applied as foliar. The treatments were applied in a complete randomized design (CRD) with three replications. Results showed that 20 CoSO4 with proline showed improvement in shoot length (∼ 20%), root length (∼ 23%), plant dry weight (∼ 19%), and plant fresh weight (∼ 41%) compared to control. The significant increase in chlorophyll, physiological and biochemical attributes of radish plants compared to the control confirms the efficacy of 20 CoSO4 in conjunction with 10 mg/L proline for mitigating salinity stress. In conclusion, application of cobalt with proline can help to alleviate salinity stress in radish plants. However, multiple location experiments with various levels of cobalt and proline still needs in-depth investigations to validate the current findings.
Keywords: antioxidancia; kobalt; salinita; Proline; Cobalt sulfate; Radish; Salinity; Raphanus; prolin; Salt Stress; Antioxidants; Cobalt; Salinity stress; Antioxidant enzymes; solný stres